Implementasi Sistem ISO 14001 dalam Pengelolaan Limbah Industri Farmasi di Indonesia - Hairunnisa Hairunnisa; Salma Fitriyanti; Nor Latifah (An-Najat, 2025)
This review explores the implementation of ISO 14001 in pharmaceutical waste management within Indonesia’s industry context. ISO 14001, as an Environmental Management System (EMS), offers a structured approach to reducing environmental risks and improving operational efficiency. The review analyzes five peer-reviewed articles published between 2023 and 2025, focusing on hospitals and pharmaceutical-related sectors. Findings reveal that ISO 14001 adoption contributes significantly to better waste segregation, reduced environmental impact, and enhanced organizational sustainability when implemented comprehensively. However, challenges such as lack of cross-unit coordination, limited policy support, and inadequate staff training hinder full system integration. The review also identifies the synergy of ISO 14001 with other standards such as ISO 45001 and ISO 22000 as a strategic advantage for industry-wide performance. Implications suggest the need for stronger regulatory frameworks and internal organizational commitment to transform ISO 14001 from a compliance tool into a driver of sustainable innovation.